Paleopathology in Southern South America: Recent advances and future challenges - Suby, Jorge Alejandro (2019)
Despite disparities among countries, paleopathology experienced a remarkabledevelopment in South America during the last years, including current theoreticalapproaches and new methodological procedures. More specialists on bone and dentalpaleopathology offered relevant information in local, regional and international journals and conferences. Some Southern South American countries, particularly Chile and Argentina, are leaders in the recent progress of paleopathology in the Americas. In this paper we summarize the recent past and present of paleopathological research in Southern South America and offer additional considerations about the challenges that need to be confronted in the near future.